Wear-resistant metal composite hammer head and preparation method thereof

Through the coordinated cooperation of rare earths, chromium, titanium, manganese and modified deterioration agent, the alloy element matching and the preparation method of deterioration agent are optimized, and the problem of insufficient wear resistance of metal hammer heads in the prior art is solved, and the wear resistance of alloys is achieved Significant improvement in properties and antioxidant properties.

CN119464943APending Publication Date: 2025-02-18CHINA COAL ZHANGJIAKOU COAL MINING MACHINERY +1
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202411657656.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-19
Publication Date
2025-02-18

AI Technical Summary

Technical Problem

The prior art has limitations in improving the wear resistance of metal hammer heads. It is difficult to effectively solve the wear problem by relying solely on alloy ratios, and the uneven dispersion of the deteriorating agent leads to a decrease in wear resistance.

Method used

Through the coordinated coordination of rare earths, chromium, titanium, manganese and modified deterioration agents, the alloy element matching and the preparation method of deterioration agent are optimized, and the fine precipitation phase and hard carbide phase are formed to improve the fluidity and wear resistance of the alloy.

Benefits of technology

The wear resistance of metal composite hammer heads has been improved, the oxidation resistance and corrosion resistance of the alloy are enhanced, the hardenability and tempering hardness of the hammer heads have been improved, and the service life is extended.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119464943A_ABST
    Figure CN119464943A_ABST
Patent Text Reader

Abstract

The invention discloses a wear-resistant metal composite hammerhead and a preparation method thereof, and belongs to the technical field of preparation of mechanical equipment crusher hammerheads. Comprising the following raw materials in percentage by weight: 20%-32.5% of scrap steel, 21%-26% of pig iron, 1%-3% of rare earth ferrosilicon alloy, 28%-36% of ferrochromium alloy, 8%-12% of ferrotitanium alloy, 4%-7% of high-carbon manganese steel and 0.5%-1% of a modified alterant. According to the invention, the wear resistance of the metal composite hammer head is improved through the synergistic cooperation of rare earth, chromium, titanium, manganese and the modified alterant.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of hammer preparation for mechanical equipment crushers, and in particular relates to a wear-resistant metal composite hammer and a preparation method thereof. Background Art

[0002] With the rapid development of economy, science and technology, and industry, mechanical equipment is also accelerating. The operation of mechanical equipment will produce friction and wear, which will cause the workpiece or equipment to fail. As the speed of equipment operation increases, the speed at which the parts subject to friction are worn will also increase, and the losses will become greater and greater. In particular, the hammer head of the crusher used in industries such as mining, metallurgy, roads, and electricity is a particularly easy-to-wear component. Friction and wear will hardly cause catastrophic damage to workpieces or equipment, but it will lead to unnecessary consumption of energy and materials, thereby increasing costs. According to statistics, about half of the energy today is consumed in friction and wear, and friction and wear will also cause the loss of metal materials on most equipment or components, thereby causing equipment or components to fail.

[0003] According to the type of wear, it can be divided into adhesive wear, abrasive wear, fatigue wear and corrosive wear: (1) Adhesive wear: It means that when two contact surfaces are in friction motion, the contact point will be continuously sheared as the motion progresses, causing the material on the contact surface to transfer. This phenomenon is adhesive wear. According to adhesion theory, the surface of metal materials in friction contact is not absolutely smooth. There will be some micro-protrusions. In addition, the friction surface is also affected by external loads. When the external load does not reach the yield strength of the material, the micro-protrusions will deform as the external load increases, thereby increasing the contact area between the micro-protrusions and the friction surface. This will continue until the actual contact area between the micro-protrusions and the friction surface can support the external load. During relative motion, the interface film will be damaged and broken, and then a new contact point will be formed at the place of friction contact. If the friction motion continues, the contact adhesion point will be sheared off, and then a new contact adhesion point will be formed. In this repetitive process, the friction contact surface continues to undergo adhesive wear. (2) Abrasive wear: Wear caused by the transfer of materials due to the action of hard particles or micro-protrusions is caused by the cross-contact stress generated by the abrasive on the contact surface. (3) Fatigue wear: When the contact surfaces of the friction pairs are in relative motion, under the action of periodic loads, the contact surfaces produce large periodic contact stresses. Under the action of this periodic contact stress, the contact surfaces will periodically produce plastic deformation. As the contact time increases, cracks will be generated in the more vulnerable parts of the contact surface due to material fatigue. The cracks will continue to expand. When the cracks extend to a certain extent, they will cause the most vulnerable parts to break and peel off. This is the so-called surface fatigue wear; (4) Corrosion wear: During the relative motion between the friction contact surfaces, the materials in the contact surface and the surrounding medium produce chemical or electrochemical changes, which in turn cause damage to the contact surface material. This is usually a relatively small amount of wear, but when the external environment changes, such as high temperature and humid environment or special corrosive media, this can turn ordinary corrosion wear into severe wear.

[0004] Patent CN117051322A discloses a high-vanadium wear-resistant alloy and a preparation method thereof. The invention controls the contents of C and V to ensure that primary carbide VC can be obtained, and the content and shape of VC are ensured, and then combines trace elements N, Nb, Mo, Ni, B and Co. While improving the wear resistance of the alloy, the toughness of the matrix is ​​improved, so that the high-vanadium wear-resistant alloy finally prepared has higher hardness, better wear resistance, and certain impact toughness.

[0005] Patent CN116516257A discloses a method for preparing a highly wear-resistant alloy and its laser cladding layer. The C and Si of the invention can form α-silicon carbide hard phase during the laser cladding process, which plays a role in improving hardness and bonding strength. Cr can form (Fe, Cr)3C phase, thereby reducing the crack sensitivity of the laser cladding layer, improving wear resistance, and improving impact resistance; Mo and W can form Fe3(W, Mo)C, W2C and other phases, improving the bonding strength, hardness, wear resistance, impact resistance, etc. of the material. Appropriate Mn content can also form (Fe, Mn)3C, which is beneficial to the wear resistance and impact resistance of the material. V is beneficial to the bonding strength and wear resistance of the material, and can also reduce grain boundary carbides, which is beneficial to improving impact resistance.

[0006] Patent CN115976413A discloses wear-resistant alloy cast steel and its preparation method and application. The invention controls the element composition and ratio in the wear-resistant alloy cast steel and combines it with two metamorphic treatments to achieve multi-level grain refinement, which is conducive to the formation of more hard phases. After heat treatment, a reasonable ratio of Cr and C allows hard carbide particles to be formed in the cast steel, taking into account both the wear resistance and toughness of the cast steel.

[0007] Patent CN113388786A discloses an ultra-strength wear-resistant alloy and its preparation process. The invention improves the wear resistance by adding covering material A, forming a first protective layer by pouring it on the outer layer of the alloy body, and forming a second protective layer by thermal spraying. The nickel base in the covering material A can form a solid solution with many elements, which is beneficial to connecting the covering material B and the metal matrix. The carbon nanotubes and graphene in the covering material B are cross-linked to form a three-dimensional network structure. Zirconium oxide and aluminum oxide are interspersed in the network structure, which improves the wear resistance and hardness.

[0008] The above invention mainly aims at solving the wear resistance problem by alloy ratio, but the wear of metal materials is a process affected by many factors, and its production mechanism is also complex and changeable. Relying solely on a single raw material ratio for modification not only has a large workload, but also sometimes has little effect. Modifiers play an important role in improving the wear resistance of alloys, but due to the size of the modifier particles, the initial mixing is prone to uneven dispersion, which can easily lead to the adverse effect that the wear resistance of the prepared alloy decreases instead of increases.

[0009] In view of this, the present invention intends to solve the problem of wear resistance of metal hammer head by studying the combination of different alloy elements with modifiers. Summary of the invention

[0010] In view of the deficiencies of the prior art, the present invention improves the wear resistance of the metal composite hammer head by synergistically combining rare earth, chromium, titanium, manganese and a modifying agent. Specifically, the technical solution of the present invention includes the following contents:

[0011] A wear-resistant metal composite hammer head, comprising a metal composite hammer head and a handle fixedly connected thereto, wherein the wear-resistant metal composite hammer head comprises the following raw materials in weight percentage:

[0012] 20% to 32.5% scrap steel, 21% to 26% pig iron, 1% to 3% rare earth ferrosilicon alloy, 28% to 36% ferrochrome alloy, 8% to 12% ferrotitanium alloy, 4% to 7% high carbon manganese steel and 0.5% to 1% modifying agent.

[0013] Furthermore, the chemical composition of the scrap steel is as follows:

[0014] C: 0.723%, Cr: 0.024%, Si: 0.225%, Mn: 0.61%, Ni: 0.013%, Cu: 0.018%, the balance is Fe and unavoidable impurities;

[0015] The chemical composition of the pig iron is as follows:

[0016] C: 4.11%, S: 0.018%, P: 0.032%, Si: 1.415%, Cr: 0.157%, Mn: 0.274%, Cu: 0.022%, the balance is iron and unavoidable impurities;

[0017] The chemical composition of the rare earth ferrosilicon alloy is as follows:

[0018] Re: 29.1%, Ca: 4.17%, Si: 43.4%, Mn: 2.65%, Ti: 2.71%, the balance is iron and unavoidable impurities;

[0019] The chemical composition of the ferrochrome alloy is as follows:

[0020] C: 0.105%, Cr: 66.7%, Si: 1.42%, P: 0.03%, S: 0.025%, the balance is iron and unavoidable impurities;

[0021] The chemical composition of the titanium-iron alloy is as follows:

[0022] Ti: 40.2%, Al: 6.01%, Si: 4.32%, Mn: 1.27%, C: 0.051%, P: 0.028%, S: 0.032%, the balance is iron and unavoidable impurities;

[0023] The chemical composition of the high carbon manganese steel is as follows:

[0024] Mn: 65.2%, C: 5.97%, P: 0.28%, S: 0.026%, Si: 2.59%, and the balance is iron and inevitable impurities.

[0025] Furthermore, the preparation method of the modified modifier comprises the following steps:

[0026] A high temperature resistant silane coupling agent, a mixed solvent, deionized water and hydrochloric acid are mixed to form a reaction system, and the reaction system is heated to 50° C. to 60° C. and reacted for 2 h to 4 h to obtain a hydrolyzate;

[0027] The modifier is dispersed in the hydrolyzate with an ultrasonic power of 300W to 400W to form a dispersion, and the dispersion is heated to 80°C to 90°C for reflux reaction for 5h to 10h to obtain the modified modifier.

[0028] Furthermore, the high temperature resistant silane coupling agent includes mercaptopropyltrimethoxysilane, vinyltri(2-methoxyethoxy)silane or 2-(3,4-epoxycyclohexyl)ethyltrimethoxysilane.

[0029] Furthermore, the mixed solvent is prepared by mixing cyclohexane and acetone in a mass ratio of 1:1.

[0030] Furthermore, the mass concentration of the hydrochloric acid is 10%.

[0031] Furthermore, the mass ratio of the high temperature resistant silane coupling agent: mixed solvent: deionized water: hydrochloric acid is 1:3:100-200:0.1-0.5.

[0032] Furthermore, the modifier includes a silicon carbide modifier, and the surface of the silicon carbide modifier has a silanol functional group, which can be chemically combined with the high temperature resistant coupling agent to achieve dispersion of the silicon carbide modifier.

[0033] Furthermore, the mass ratio of the deteriorating agent to the hydrolyzate is 1:50-100.

[0034] A method for preparing a wear-resistant metal composite hammer head, the method comprising the following steps:

[0035] Putting scrap steel, pig iron, rare earth ferrosilicon alloy, ferrochrome alloy, ferrotitanium alloy, high carbon manganese steel and modified modifier into a smelting furnace, and smelting at 1500°C to 1650°C for 35min to 45min to obtain casting liquid;

[0036] After the casting liquid is poured, the temperature is lowered to 950° C. to 1050° C. and quenched for 25 min to 30 min, and then tempered at 260° C. to 320° C. for 1.5 h to 2.5 h to obtain the wear-resistant metal composite hammer head.

[0037] Compared with the prior art, the present invention has the following beneficial effects:

[0038] The invention enhances the strength and toughness of the metal matrix by introducing rare earth elements. The rare earth elements can improve the fluidity of the alloy, form fine precipitation phases, facilitate deoxidation, degassing and inclusion removal, and can make the grains finer and the grain boundaries clearer, and also change the morphology and distribution of carbides. Chromium has a strong ability to combine with carbon elements, and the generated carbides mainly improve the hardenability and tempering hardness of the material, and enhance the anti-oxidation and anti-corrosion capabilities of the material. Titanium has high-temperature solubility, so that fine grain structure can be obtained during the heat treatment process, dendrite segregation can be reduced, the strength and toughness of the metal material can be improved, very stable TiC can be formed, and aging sensitivity and cold brittleness can be reduced. Manganese can also refine the grains, thereby improving the strength and hardness of the metal material, and manganese has strong deoxidation and desulfurization capabilities, can strengthen the metal material, increase the dispersion and stability of carbides, and significantly improve the hardenability of the metal. Silicon carbide, as a modifier material with extremely high hardness, can act as a reinforcing phase to hinder dislocation movement and improve the wear resistance of metal materials. However, due to the uneven dispersion of silicon carbide, it is easy to agglomerate and cause stress concentration, which in turn affects the wear resistance of the metal. It is modified by a high-temperature resistant silane coupling agent to achieve pre-dispersion to obtain a modified modifier, thereby improving the grain refinement performance of the modifier during the smelting process of metal materials. The polysiloxane obtained by self-crosslinking condensation of the high-temperature resistant silane coupling agent has high temperature resistance and can prolong the dispersion time of the silicon carbide modifier. As the melting temperature increases, the polysiloxane can be evaporated and removed from the system to avoid the influence of excessive silicon on the metal material. Through the synergistic combination of rare earth, chromium, titanium, manganese and modifying agents, chromium can promote the formation of hard phase together with titanium and improve the wear resistance of the alloy; rare earth elements can improve the casting quality, while manganese can improve the toughness, making the alloy less likely to break when impacted; the good combination between silicon carbide and the metal matrix can not only form a hard carbide phase (Fe3C, etc.), but also improve the flowability of liquid metal during the smelting process, reduce the generation of defects such as pores, and thus enhance the wear resistance of the alloy, ultimately achieving the improvement of the wear resistance of the metal composite hammer. BRIEF DESCRIPTION OF THE DRAWINGS

[0039] Figure 1 This is a schematic diagram of the structure of the wear-resistant metal composite hammer head after assembly of the present invention.

[0040] In the figure, 1-metal-resistant composite hammer head, 2-handle. DETAILED DESCRIPTION

[0041] The technical solution of the present invention will be clearly and completely described below through the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by those skilled in the art without creative work are within the scope of protection of the present invention.

[0042] Unless otherwise specified, the raw materials and reagents used in the present invention are commercially available or can be prepared by known methods.

[0043] Rare earth ferrosilicon alloy, ferrochrome alloy and ferrotitanium alloy are all purchased from Xi'an Qinli Alloy Material Technology Co., Ltd.;

[0044] Pig iron is purchased from Liaoyang Dexin Casting Co., Ltd.

[0045] High carbon manganese steel was purchased from Shanghai Shenyun Ferroalloy Co., Ltd.;

[0046] Silicon carbide modifier was purchased from Zhengzhou Shengyuan Casting Co., Ltd.

[0047] Preparation Example 1:

[0048] The preparation of the modified modifier specifically includes the following processes:

[0049] 100g of mercaptopropyltrimethoxysilane was dispersed in 300g of mixed solvent (150g of cyclohexane and 150g of acetone) to form a mixed solution, and then the mixed solution was added to 10kg of deionized water and stirred evenly, and then 10g of 10% hydrochloric acid solution was added and stirred evenly to form a reaction system. The reaction system was heated to 50°C for 2h. After the reaction was completed, it was cooled to room temperature to obtain a hydrolyzate.

[0050] Take 10g of the modifier powder and add it to 500g of the hydrolyzate, then put it in an ultrasonic cleaner and disperse it at 300W of ultrasonic power for 15min to obtain a dispersion. After the dispersion is completed, the dispersion is placed in an 80°C temperature environment for reflux reaction for 5h. After the reflux is completed, the solid-liquid separation is performed by a centrifuge, and the obtained solid powder is placed in a drying oven at 55°C and dried until the weight no longer changes to obtain a modified modifier.

[0051] Preparation Example 2:

[0052] The preparation of the modified modifier specifically includes the following processes:

[0053] 100g of mercaptopropyltrimethoxysilane was dispersed in 300g of mixed solvent (150g of cyclohexane and 150g of acetone) to form a mixed solution, and then the mixed solution was added to 12kg of deionized water and stirred evenly, and then 20g of 10% hydrochloric acid solution was added and stirred evenly to form a reaction system. The reaction system was heated to 50°C for 2h. After the reaction was completed, it was cooled to room temperature to obtain a hydrolyzate.

[0054] Take 10g of the modifier powder and add it to 600g of the hydrolyzate, then put it in an ultrasonic cleaner and disperse it at 320W of ultrasonic power for 16 minutes to obtain a dispersion. After the dispersion is completed, the dispersion is placed in an 80°C temperature environment for reflux reaction for 6 hours. After the reflux is completed, the solid-liquid separation is performed by a centrifuge, and the obtained solid powder is placed in a drying oven at 55°C and dried until the weight no longer changes to obtain a modified modifier.

[0055] Preparation Example 3:

[0056] The preparation of the modified modifier specifically includes the following processes:

[0057] 100g of vinyl tri(2-methoxyethoxy)silane was dispersed in 300g of a mixed solvent (150g of cyclohexane and 150g of acetone) to form a mixed solution, and then the mixed solution was added to 14kg of deionized water and stirred evenly, and then 30g of a 10% hydrochloric acid solution was added and stirred evenly to form a reaction system. The reaction system was heated to 55°C and reacted for 3h. After the reaction was completed, it was cooled to room temperature to obtain a hydrolyzate.

[0058] Take 10g of the modifier powder and add it to 700g of the hydrolyzate, then put it in an ultrasonic cleaner and disperse it at 340W of ultrasonic power for 17min to obtain a dispersion. After the dispersion is completed, the dispersion is placed in an 85°C temperature environment for reflux reaction for 7h. After the reflux is completed, the solid-liquid separation is performed by a centrifuge, and the obtained solid powder is placed in a drying oven at 55°C and dried until the weight no longer changes to obtain a modified modifier.

[0059] Preparation Example 4:

[0060] The preparation of the modified modifier specifically includes the following processes:

[0061] 100g of vinyl tris(2-methoxyethoxy)silane was dispersed in 300g of a mixed solvent (150g of cyclohexane and 150g of acetone) to form a mixed solution, and then the mixed solution was added to 16kg of deionized water and stirred evenly, and then 40g of a 10% hydrochloric acid solution was added and stirred evenly to form a reaction system. The reaction system was heated to 55°C for 3h. After the reaction was completed, it was cooled to room temperature to obtain a hydrolyzate.

[0062] Take 10g of the modifier powder and add it to 800g of the hydrolyzate, then put it in an ultrasonic cleaning machine and disperse it at 360W of ultrasonic power for 18 minutes to obtain a dispersion. After the dispersion is completed, the dispersion is placed in an 85°C temperature environment for reflux reaction for 8 hours. After the reflux is completed, the solid-liquid separation is performed by a centrifuge, and the obtained solid powder is placed in a drying oven at 55°C and dried until the weight no longer changes to obtain a modified modifier.

[0063] Preparation Example 5:

[0064] The preparation of the modified modifier specifically includes the following processes:

[0065] 100g of 2-(3,4-epoxycyclohexyl)ethyltrimethoxysilane was dispersed in 300g of mixed solvent (150g of cyclohexane and 150g of acetone) to form a mixed solution, and then the mixed solution was added to 18kg of deionized water and stirred evenly, and then 50g of 10% hydrochloric acid solution was added and stirred evenly to form a reaction system. The reaction system was heated to 60°C and reacted for 4h. After the reaction was completed, it was cooled to room temperature to obtain a hydrolyzate.

[0066] Take 10g of the modifier powder and add it to 900g of the hydrolyzate, then put it in an ultrasonic cleaning machine and disperse it at 380W of ultrasonic power for 19 minutes to obtain a dispersion. After the dispersion is completed, the dispersion is placed in a 90°C temperature environment for reflux reaction for 9 hours. After the reflux is completed, the solid-liquid separation is performed by a centrifuge, and the obtained solid powder is placed in a drying oven at 55°C and dried until the weight no longer changes to obtain a modified modifier.

[0067] Preparation Example 6:

[0068] The preparation of the modified modifier specifically includes the following processes:

[0069] 100g of 2-(3,4-epoxycyclohexyl)ethyltrimethoxysilane was dispersed in 300g of mixed solvent (150g of cyclohexane and 150g of acetone) to form a mixed solution, and then the mixed solution was added to 20kg of deionized water and stirred evenly, and then 50g of 10% hydrochloric acid solution was added and stirred evenly to form a reaction system. The reaction system was heated to 60°C and reacted for 4h. After the reaction was completed, it was cooled to room temperature to obtain a hydrolyzate.

[0070] Take 10g of the modifier powder and add it to 1000g of the hydrolyzate, then put it in an ultrasonic cleaner and disperse it at 400W ultrasonic power for 20min to obtain a dispersion. After the dispersion is completed, the dispersion is placed in a 90℃ temperature environment for reflux reaction for 10h. After the reflux is completed, the solid-liquid separation is performed by a centrifuge, and the obtained solid powder is placed in a drying oven at 55℃ and dried until the weight no longer changes to obtain a modified modifier.

[0071] Preparation Example 7:

[0072] The preparation of the modified modifier specifically includes the following processes:

[0073] The amount of 2-(3,4-epoxycyclohexyl)ethyltrimethoxysilane in Preparation Example 6 was increased to 200 g, and the other conditions remained the same as in Preparation Example 6.

[0074] Preparation Example 8:

[0075] The preparation of the modified modifier specifically includes the following processes:

[0076] Take 10g of the modifier powder and add it to 1000g of acrylic acid solution, then put it in an ultrasonic cleaning machine and disperse it at 400W ultrasonic power for 20min to obtain a dispersion. After the dispersion is completed, add 5g of azobisisobutyronitrile and mix it with the dispersion, and place the mixed dispersion in an environment of 80℃ for reflux reaction for 10h. After the reflux is completed, the solid-liquid separation is carried out by a centrifuge, and the obtained solid powder is placed in a drying oven at 55℃ and dried until the weight no longer changes to obtain a modified modifier.

[0077] Embodiment 1:

[0078] A preparation method of a wear-resistant metal composite hammer head specifically includes the following processes:

[0079] The smelting furnace is preheated first. After the preheating is completed, 32.5% scrap steel, 26% pig iron, 1% rare earth ferrosilicon alloy, 28% ferrochrome alloy, 8% ferrotitanium alloy, 4% high carbon manganese steel and 0.5% modified modifier obtained in Preparation Example 1 are put into the smelting furnace for smelting according to weight percentage. After all are melted, the temperature is controlled to 1500°C and smelted at this temperature for 35 minutes. After the smelting is completed, the casting liquid is poured into the mold, and then quenched in a resistance furnace at 950°C for 25 minutes. After the quenching is completed, the temperature is lowered to 260°C and tempered for 1.5 hours. Then it is naturally cooled to room temperature to obtain a wear-resistant metal composite hammer head.

[0080] Embodiment 2:

[0081] A preparation method of a wear-resistant metal composite hammer head specifically includes the following processes:

[0082] The smelting furnace is preheated first. After the preheating is completed, 31.4% scrap steel, 25% pig iron, 1% rare earth ferrosilicon alloy, 29% ferrochrome alloy, 9% ferrotitanium alloy, 4% high carbon manganese steel and 0.6% modified modifier obtained in Preparation Example 2 are put into the smelting furnace for smelting according to weight percentage. After all are melted, the temperature is controlled to 1550°C and smelted at this temperature for 35 minutes. After the smelting is completed, the casting liquid is poured into the mold, and then quenched in a resistance furnace at 950°C for 26 minutes. After the quenching is completed, the temperature is lowered to 260°C and tempered for 1.5 hours. Then it is naturally cooled to room temperature to obtain a wear-resistant metal composite hammer head.

[0083] Embodiment 3:

[0084] A preparation method of a wear-resistant metal composite hammer head specifically includes the following processes:

[0085] The smelting furnace is preheated first. After the preheating is completed, 26.3% scrap steel, 24% pig iron, 2% rare earth ferrosilicon alloy, 32% ferrochrome alloy, 10% ferrotitanium alloy, 5% high carbon manganese steel and 0.7% modified modifier obtained in Preparation Example 3 are put into the smelting furnace for smelting according to weight percentage. After all are melted, the temperature is controlled to 1550°C and smelted at this temperature for 40 minutes. After the smelting is completed, the casting liquid is poured into the mold and then quenched in a resistance furnace at 1000°C for 27 minutes. After the quenching is completed, the temperature is lowered to 280°C and tempered for 2 hours. Then it is naturally cooled to room temperature to obtain a wear-resistant metal composite hammer head.

[0086] Embodiment 4:

[0087] A preparation method of a wear-resistant metal composite hammer head specifically includes the following processes:

[0088] The smelting furnace is preheated first. After the preheating is completed, 24.2% scrap steel, 23% pig iron, 2% rare earth ferrosilicon alloy, 33% ferrochrome alloy, 11% ferrotitanium alloy, 6% high carbon manganese steel and 0.8% modified modifier obtained in Preparation Example 4 are put into the smelting furnace for smelting according to weight percentage. After all are melted, the temperature is controlled to 1600°C and smelted at this temperature for 40 minutes. After the smelting is completed, the casting liquid is poured into the mold, and then quenched in a resistance furnace at 1000°C for 28 minutes. After the quenching is completed, the temperature is lowered to 300°C and tempered for 2 hours. Then it is naturally cooled to room temperature to obtain a wear-resistant metal composite hammer head.

[0089] Embodiment 5:

[0090] A preparation method of a wear-resistant metal composite hammer head specifically includes the following processes:

[0091] The smelting furnace is preheated first. After the preheating is completed, 22.1% scrap steel, 22% pig iron, 3% rare earth ferrosilicon alloy, 35% ferrochrome alloy, 11% ferrotitanium alloy, 6% high carbon manganese steel and 0.9% modified modifier obtained in Preparation Example 5 are put into the smelting furnace for smelting according to weight percentage. After all are melted, the temperature is controlled to 1600°C and smelted at this temperature for 45 minutes. After the smelting is completed, the casting liquid is poured into the mold and then quenched in a resistance furnace at 1050°C for 29 minutes. After the quenching is completed, the temperature is lowered to 300°C and tempered for 2.5 hours. Then it is naturally cooled to room temperature to obtain a wear-resistant metal composite hammer head.

[0092] Embodiment 6:

[0093] A preparation method of a wear-resistant metal composite hammer head specifically includes the following processes:

[0094] The smelting furnace is preheated first. After the preheating is completed, 20% scrap steel, 21% pig iron, 3% rare earth ferrosilicon alloy, 36% ferrochrome alloy, 12% ferrotitanium alloy, 7% high carbon manganese steel and 1% modified modifier obtained in Preparation Example 6 are put into the smelting furnace for smelting according to weight percentage. After all are melted, the temperature is controlled to 1650°C and smelted at this temperature for 45 minutes. After the smelting is completed, the casting liquid is poured into the mold and then quenched in a resistance furnace at 1050°C for 30 minutes. After the quenching is completed, the temperature is lowered to 320°C and tempered for 2.5 hours. Then it is naturally cooled to room temperature to obtain a wear-resistant metal composite hammer head.

[0095] Comparative Example 1:

[0096] A preparation method of a wear-resistant metal composite hammer head specifically includes the following processes:

[0097] The smelting furnace is preheated first. After the preheating is completed, 20% scrap steel, 21% pig iron, 3% rare earth ferrosilicon alloy, 36% ferrochrome alloy, 12% ferrotitanium alloy, 7% high carbon manganese steel and 1% modified modifier obtained in Preparation Example 7 are put into the smelting furnace for smelting according to weight percentage. After all are melted, the temperature is controlled to 1650°C and smelted at this temperature for 45 minutes. After the smelting is completed, the casting liquid is poured into the mold and then quenched in a resistance furnace at 1050°C for 30 minutes. After the quenching is completed, the temperature is lowered to 320°C and tempered for 2.5 hours. Then it is naturally cooled to room temperature to obtain a wear-resistant metal composite hammer head.

[0098] Comparative Example 2:

[0099] A preparation method of a wear-resistant metal composite hammer head specifically includes the following processes:

[0100] The smelting furnace is preheated first. After the preheating is completed, 20% scrap steel, 21% pig iron, 3% rare earth ferrosilicon alloy, 36% ferrochrome alloy, 12% ferrotitanium alloy, 7% high carbon manganese steel and 1% modified modifier obtained in Preparation Example 8 are put into the smelting furnace for smelting according to weight percentage. After all are melted, the temperature is controlled to 1650°C and smelted at this temperature for 45 minutes. After the smelting is completed, the casting liquid is poured into the mold, and then quenched in a resistance furnace at 1050°C for 30 minutes. After the quenching is completed, the temperature is lowered to 320°C and tempered for 2.5 hours. Then it is naturally cooled to room temperature to obtain a wear-resistant metal composite hammer head.

[0101] Comparative Example 3:

[0102] A preparation method of a wear-resistant metal composite hammer head specifically includes the following processes:

[0103] The smelting furnace is preheated first. After the preheating is completed, 20% scrap steel, 19% pig iron, 3% rare earth ferrosilicon alloy, 30% ferrochrome alloy, 20% ferrotitanium alloy, 7% high carbon manganese steel and 1% modified modifier obtained in Preparation Example 6 are put into the smelting furnace for smelting according to weight percentage. After all are melted, the temperature is controlled to 1650°C and smelted at this temperature for 45 minutes. After the smelting is completed, the casting liquid is poured into the mold and then quenched in a resistance furnace at 1050°C for 30 minutes. After the quenching is completed, the temperature is lowered to 320°C and tempered for 2.5 hours. Then it is naturally cooled to room temperature to obtain a wear-resistant metal composite hammer head.

[0104] Comparative Example 4:

[0105] A preparation method of a wear-resistant metal composite hammer head specifically includes the following processes:

[0106] The smelting furnace is preheated first. After the preheating is completed, 17% scrap steel, 17% pig iron, 3% rare earth ferrosilicon alloy, 35% ferrochrome alloy, 12% ferrotitanium alloy, 15% high carbon manganese steel and 1% modified modifier obtained in Preparation Example 6 are put into the smelting furnace for smelting according to weight percentage. After all are melted, the temperature is controlled to 1650°C and smelted at this temperature for 45 minutes. After the smelting is completed, the casting liquid is poured into the mold and then quenched in a resistance furnace at 1050°C for 30 minutes. After the quenching is completed, the temperature is lowered to 320°C and tempered for 2.5 hours. Then it is naturally cooled to room temperature to obtain a wear-resistant metal composite hammer head.

[0107] The wear resistance of the wear-resistant metal composite hammers obtained in Examples 1 to 6 and Comparative Examples 1 to 4 was verified using a friction and wear tester, with a test force of 220 N, a rotation speed of 200 r / min, and a wear time of 60 min. The results are shown in Table 1 below.

[0108] Table 1

[0109] Sources Relative wear resistance Example 1 1.23 Example 2 1.34 Example 3 1.41 Example 4 1.55 Example 5 1.61 Example 6 1.62 Comparative Example 1 0.48 Comparative Example 2 0.87 Comparative Example 3 1.01 Comparative Example 4 1.14

[0110] The following conclusions can be drawn from the data in the above table:

[0111] (1) In Examples 1 to 6 of the present invention, through the synergistic combination of rare earth, chromium, titanium, manganese and modifying agents, chromium can promote the formation of hard phases together with titanium, thereby improving the wear resistance of the alloy; rare earth elements can improve the casting quality, while manganese can improve the toughness, making the alloy less likely to break when impacted; the good combination between silicon carbide and the metal matrix can not only form a hard carbide phase (Fe3C, etc.), but also improve the flowability of the liquid metal during the smelting process, reduce the generation of defects such as pores, and thus enhance the wear resistance of the alloy, ultimately achieving the improvement of the wear resistance of the metal composite hammer.

[0112] (2) It can be found from Comparative Example 1 that the increase in the amount of high-temperature resistant 2-(3,4-epoxycyclohexyl)ethyltrimethoxysilane used leads to excessive condensation polymerization between too many silane coupling agents, which in turn further agglomerates silicon carbide, making it unfavorable for use and resulting in poor wear resistance.

[0113] (3) Comparative Example 2 shows that although acrylic acid can disperse silicon carbide through carboxylic acid groups, the polyacrylic acid obtained after dispersion has lower high temperature resistance than the polysiloxane obtained by cross-linking with a silane coupling agent, and cannot extend the dispersion time of silicon carbide. As a result, the polyacrylic acid evaporates too quickly when encountering high temperature and is removed from the system, resulting in the inability to effectively disperse silicon carbide, which is not conducive to the role of the modifier and has poor wear resistance.

[0114] (4) It can be found from Comparative Example 3 that although titanium can combine with carbon to form hard phase carbides with strengthening and refining effects during the smelting process, under the system constructed by the present invention, the amount of titanium is further increased, and the excess titanium is dissolved in the ferrite, causing ferrite catalysis, offsetting the effect of grain refinement, and deteriorating the performance.

[0115] (5) It can be found from Comparative Example 4 that although manganese can improve the toughness of the alloy and reduce the brittle phase in the alloy, in the system of the present invention, too much manganese will increase the overheating sensitivity and temper brittleness of the alloy, making the grains coarse, which will reduce the wear resistance of the material.

[0116] The above-described embodiments provide a detailed description of the technical solutions and beneficial effects of the present invention. It should be understood that the above description is only a specific embodiment of the present invention and is not intended to limit the present invention. Without departing from the spirit and scope of the present invention, the present invention may have various changes and improvements, which fall within the scope of the present invention to be protected.

Claims

1. A wear-resistant metal composite hammer head, comprising a wear-resistant metal composite hammer head (1) and a handle (2) fixedly connected thereto, characterized in that: The wear-resistant metal composite hammer head comprises the following raw materials in weight percentage: 20% to 32.5% scrap steel, 21% to 26% pig iron, 1% to 3% rare earth ferrosilicon alloy, 28% to 36% ferrochrome alloy, 8% to 12% ferrotitanium alloy, 4% to 7% high carbon manganese steel and 0.5% to 1% modifying agent.

2. A wear-resistant metal composite hammer head according to claim 1, characterized in that: The preparation method of the modified modifier comprises the following steps: A high temperature resistant silane coupling agent, a mixed solvent, deionized water and hydrochloric acid are mixed to form a reaction system, and the reaction system is heated to 50° C. to 60° C. and reacted for 2 h to 4 h to obtain a hydrolyzate; The modifier is dispersed in the hydrolyzate with an ultrasonic power of 300W to 400W to form a dispersion, and the dispersion is heated to 80°C to 90°C for reflux reaction for 5h to 10h to obtain the modified modifier.

3. A wear-resistant metal composite hammer head according to claim 2, characterized in that: The high temperature resistant silane coupling agent includes mercaptopropyltrimethoxysilane, vinyltri(2-methoxyethoxy)silane or 2-(3,4-epoxycyclohexyl)ethyltrimethoxysilane.

4. A wear-resistant metal composite hammer head according to claim 2, characterized in that: The mixed solvent is prepared by mixing cyclohexane and acetone in a mass ratio of 1:

1.

5. The wear-resistant metal composite hammer head according to claim 2, characterized in that: The mass concentration of the hydrochloric acid is 10%.

6. The wear-resistant metal composite hammer head according to claim 2, characterized in that: The mass ratio of the high temperature resistant silane coupling agent: the mixed solvent: the deionized water: the hydrochloric acid is 1:3: 100-200: 0.1-0.

5.

7. The wear-resistant metal composite hammer head according to claim 2, characterized in that: The modifier includes a silicon carbide modifier.

8. The wear-resistant metal composite hammer head according to claim 2, characterized in that: The mass ratio of the deteriorating agent to the hydrolyzate is 1:50-100.

9. A method for preparing a wear-resistant metal composite hammer head as claimed in any one of claims 1 to 8, characterized in that: The preparation method comprises the following steps: Putting scrap steel, pig iron, rare earth ferrosilicon alloy, ferrochrome alloy, ferrotitanium alloy, high carbon manganese steel and modified modifier into a smelting furnace, and smelting at 1500°C to 1650°C for 35min to 45min to obtain casting liquid; After the casting liquid is poured, the temperature is lowered to 950° C. to 1050° C. and quenched for 25 min to 30 min, and then tempered at 260° C. to 320° C. for 1.5 h to 2.5 h to obtain the wear-resistant metal composite hammer head.

Citation Information

Patent Citations

  • Super-strength wear-resistant alloy and preparation process thereof

    CN113388786A